2014
DOI: 10.1073/pnas.1410943111
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin processivity is gated by phosphate release

Abstract: Kinesin-1 is a dimeric motor protein, central to intracellular transport, that steps hand-over-hand toward the microtubule (MT) plus-end, hydrolyzing one ATP molecule per step. Its remarkable processivity is critical for ferrying cargo within the cell: over 100 successive steps are taken, on average, before dissociation from the MT. Despite considerable work, it is not understood which features coordinate, or "gate," the mechanochemical cycles of the two motor heads. Here, we show that kinesin dissociation occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
296
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(335 citation statements)
references
References 40 publications
31
296
1
Order By: Relevance
“…S1), strongly suggesting that under physiological conditions, hydrolysis occurs before tethered head attachment. Milic and coworkers recently showed that processivity under assisting load is not increased in ATPγS but is increased by adding phosphate to the media, in support of ATP hydrolysis occurring before tethered head attachment (19,41). We extend that result by showing that in a zero-load assay the run length in ATPγS is not higher than the run length in ATP (Fig.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…S1), strongly suggesting that under physiological conditions, hydrolysis occurs before tethered head attachment. Milic and coworkers recently showed that processivity under assisting load is not increased in ATPγS but is increased by adding phosphate to the media, in support of ATP hydrolysis occurring before tethered head attachment (19,41). We extend that result by showing that in a zero-load assay the run length in ATPγS is not higher than the run length in ATP (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…If hydrolysis can occur in either a 1HB or 2HB state, then run length should increase in ATPγS because the tethered head would have a much greater chance to bind before the bound head hydrolyzes its nucleotide and enters a vulnerable 1HB posthydrolysis state (19). The opposite was observed-in single-molecule Qdot-tracking experiments, run lengths were slightly shorter in saturating ATPγS than in saturating ATP (Fig.…”
Section: Significancementioning
confidence: 94%
See 3 more Smart Citations